Spectroscopic analysis reveals the effect of a single nucleotide bulge on G-quadruplex structures. Issue 18 (6th February 2019) - Chan, Chun-Yin; Umar, Mubarak I.; Kwok, Chun Kit
Abstract : This work employs multiple spectroscopic assays to examine the effect of the position and identity of a single-nucleotide bulge on G-quadruplex (G4). Abstract : Here we investigate and reveal the effect of bulge position and bulge identity on G-quadruplexes using label-free spectroscopic techniques. Notably, we report significant differences in the spectroscopic features of bulged DNA and RNA G-quadruplexes, and demonstrate that intrinsic fluorescence can be generally used to detect the formation of canonical and non-canonical G-quadruplexes.